Honeybee queen mandibular pheromone induces a starvation response in Drosophila melanogaster. - Lovegrove, M.R.; Dearden, P.K.; Duncan, E.J. (Insect Biochemistry and Molecular Biology, 2023)
Eusocial insect societies are defined by the reproductive division of labour, a social structure that is generally enforced by the reproductive dominant(s) or 'queen(s)'. Reproductive dominance is maintained through behavioural dominance or production of queen pheromones, or a mixture of both. Queen mandibular pheromone (QMP) is a queen pheromone produced by queen honeybees (Apis mellifera) which represses reproduction in worker honeybees. How QMP acts to repress worker reproduction, the mechanisms by which this repression is induced, and how it has evolved this activity, remain poorly understood. Surprisingly, QMP is capable of repressing reproduction in non-target arthropods. Here we show that in Drosophila melanogaster QMP treatment mimics the starvation response, disrupting reproduction. QMP exposure induces an increase in food consumption and activation of checkpoints in the ovary that reduce fecundity and depresses insulin signalling. The magnitude of these effects is indistinguishable between QMP-treated and starved individuals. As QMP triggers a starvation response in an insect diverged from honeybees, we propose that QMP originally evolved by co-opting nutrition signalling pathways to regulate reproduction.